Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2010
DOI: 10.1145/1753326.1753468
|View full text |Cite
|
Sign up to set email alerts
|

Tools-at-hand and learning in multi-session, collaborative search

Abstract: Improving search interfaces and algorithms are major foci of HCI and information retrieval (IR) research respectively. However, less attention has been given to understanding how users collect, manage, organize, and share the results they find from conducting searches on the Web and designing tools to support their needs. In this paper, we present results from a study in which we interviewed 30 people in three cohorts (academic researchers, corporate workers, and people looking for medical information) about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…To manage the information load that complex search tasks generate, searchers tend to make heavy use of bookmarking, re-searching to locate previously seen content, and printing, emailing and saving pages [4], [16]. A number of features exist within experimental search systems to support complex search tasks, although studies have shown that these features are rarely found in the wild [11].…”
Section: Related Workmentioning
confidence: 99%
“…To manage the information load that complex search tasks generate, searchers tend to make heavy use of bookmarking, re-searching to locate previously seen content, and printing, emailing and saving pages [4], [16]. A number of features exist within experimental search systems to support complex search tasks, although studies have shown that these features are rarely found in the wild [11].…”
Section: Related Workmentioning
confidence: 99%
“…For this purpose we chose the 5000 most frequent English words from the Brown Corpus [37]. 2 Stop words [38], bigrams and contractions, such as I'd were removed, leaving 4632 words. We sampled the most frequent English words, because we do not have access to the frequency distribution of the whole BNC.…”
Section: Hit Count Prediction Modelmentioning
confidence: 99%
“…Workshops Much of the research to date has focused on synchronous collaborative search, in which people sit at different computers, but conduct searches at the same time. However, several recent surveys have shown that people do a significant amount of asynchronous collaborative searching [2] [4] and that existing tools do not support this activity well [1]. Many users rely on simple "tools-at-hand" such as email and text documents to organize their collaborative searches [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent surveys have shown that people do a significant amount of asynchronous collaborative searching [2] [4] and that existing tools do not support this activity well [1]. Many users rely on simple "tools-at-hand" such as email and text documents to organize their collaborative searches [1]. In this project, we set out to study asynchronous collaborative search activities.…”
Section: Introductionmentioning
confidence: 99%